Evaluation of Sawdust as a Sustainable Dye Source in Ethiopia - Chandrasekaran P.; Saminathan Ratnapandian (Tekstilec, 2023)
Increasing eco-consciousness among consumers is creating an expanding niche market for textiles coloured using natural dyes. Natural dyes are derived from different parts of plants, animals (insects and invertebrates) and minerals. Although plant sources are common, a growing global population makes them compete with food crops. Hence, there is a need to investigate alternate avenues for procuring natural dyes. This research examined the feasibility of utilizing extractions of sawdust, a waste product of the wood furniture industry, as a natural colorant. Sawdust is an inevitable waste generated during the conversion of wood into consumer products such as furniture (tables, chairs, etc.), doors and windows. Sawdust, generated in significant amounts by timber mills, may be used in chipboard manufacture. However, the furniture industry disposes of sawdust as fuel or sometimes as communal waste. In this study, segregated sawdust of the most common woods was collected from Ethiopian furniture houses in Addis Ababa and Bahir Dar. Dyeing was attempted on cotton and wool fabrics using individual aqueous extractions. Different shades were obtained only on wool by simultaneous mordanting with mordants, such as copper sulphate, ferrous sulphate and potassium dichromate, using the exhaust dyeing method. Acceptable fastness to light, perspiration, rubbing and washing, as evaluated according to the relevant ISO standards, was obtained. It may be concluded that sawdust is a viable secondary source of natural dyes for textile coloration in Ethiopia and elsewhere.